Job characteristics, employee well-being, and job performance of public sector employees in Malaysia - Johari, Johanim; Mohd Shamsudin, Faridahwati; Tan, Fee Yean; Yahya, Khulida Kirana; Adnan, Zurina (Emerald Publishing Limited, 2019)
Purpose – The purpose of this paper is to examine the structural relationships between the job itself (i.e. job characteristics), employee well-being and job performance in light of the new administrative reform called the Government Transformation Program in Malaysia that stresses on measurable performance outputs. Design/methodology/approach – A total of 208 public sector employees from various public agencies and departments in the northern region of Peninsular Malaysia were surveyed. Some of the agencies that took part in the study include state departments, the fishery department, agriculture-related agencies and the rural development agency. Findings – The authors observed that feedback positively influenced employee well-being, which served as a significant mediator in the relationship between feedback and job performance. The results indicated that 26.4 percent of the variance that explained employee well-being was accounted for by the different characteristics of a job. The authors also demonstrated that employee well-being accounted for 41.8 percent of job performance. Research limitations/implications – The authors recommended that public sector managers consider the element of feedback and enhance employee well-being to improve job performance. Originality/value – This study offers an insight into the effect of perceived changes in the job itself on employee well-being and subsequent job performance in light of government reforms